Penerapan Pola Peran Optimalisasi Pengelolaan Administrasi Desa Melalui Sistem Informasi Manajemen - Siahaan, Septony; Pasaribu , Dompak; Simanjuntak, Wesly Andri; SITORUS, SUNDAY ADE; SUNDAY ADE SITORUS (LPPM Universitas HKBP Nommensen, 2025)
This service aims to implement a Management Information System (SIM) to improve the efficiency of village administration management, accelerate public services, and increase transparency in Sei Mencirim Village. This program also aims to improve the digital literacy of village officials to be able to utilize technology in managing village administration. This activity is carried out through socialization, technical training, and mentoring of village officials in using SIM. Socialization aims to provide a basic understanding of SIM, while technical training includes simulations of using SIM software and managing village administration data. The final stage is mentoring to ensure the SIM can operate optimally. The implementation of the SIM has improved the efficiency of village administration management, accelerated public services, and increased transparency of village budgets. The community felt the direct benefits in the form of faster document processing time, as well as increased transparency in budget use. Village officials can access and manage data in real-time, accelerating the decision-making process. The main challenges in implementing the SIM include limited technological infrastructure and low digital literacy of village officials. However, the training provided has improved the ability of village officials to manage administration better. The program is also credited with reducing administrative errors that are common in manual systems. However, strengthening the infrastructure and increasing the capacity of village officials are needed to optimize the operation of the SIM. The implementation of SIM in Sei Mencirim Village has brought positive impacts in the form of increased administrative efficiency and public services. Although there are still challenges such as limited infrastructure and digital literacy, this program can be used as a model for implementing technology in other villages. With the support of the local government, this program is expected to improve community welfare and encourage transparency in village management.